(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Today is certainly not a high time. And the crisis of politics in Rome will still last many years. In the worst periods, in fact, the weaknesses, the corporatism, the welfare have found protection in the state intervention, which in doing so has sterilized the autonomous capacities of the social body, further aggravating the dependence on the administration, in a vicious circuit of amplification of the income as a mode of economic organization. The weakness of politics is the occasion to interrupt these negative processes and help the Roman society to find other ways of development. It is an opportunity to experience the capital for-itself, preparing the social and cultural materials that will constitute the humus of future and innovative political experiences. The new leaderships will not be born from the current political class but only from a new social generativity.